Performance Analysis and Development Strategy of Coastal Fisheries Ports (PPP) - Arfani Mukrim; Mulyono Baskoro; Agus Santoso (Pusat Riset dan Inovasi Nasional, 2025)
This research focuses on evaluating the performance and development strategy of the Coastal Fisheries Port (PPP) in Kota Agung, located in Tanggamus Regency, Lampung Province. The results reveal that both internal and external elements influence the port’s activities and overall effectiveness, with organizational aspects emerging as a key determinant. Hypothesis testing confirms that the organizational factor (X2) has a significant effect on port performance (Y). Through the application of USG and SWOT analysis, several critical challenges were identified: (1) the need to optimize supporting facilities to enhance service quality and fish catch, (2) the necessity for funding to rehabilitate and revitalize existing land for better usage, and (3) the importance of improving fishermen's skills to support environmental sustainability around the port area. In light of these insights, the study recommends a more systematic management approach for PPP Kota Agung, emphasizing organizational improvements, efficient use of facilities, and capacity-building programs to boost performance and strengthen the port’s competitiveness.